Spinal Cord Blood Flow after Ischemic Preconditioning in a Rat Model of Spinal Cord Ischemia. (2004) - Zvara, David; Zboyovski, James M.; Deal, Dwight D.; Vernon, Jason C.; Colonna, David M.
Abstract : Spinal cord blood flow after ischemic preconditioning is poorly characterized. This study is designed to evaluate spinal cord blood flow patterns in animals after acute ischemic preconditioning. Experiment 1: After a laminectomy and placement of a laser Doppler probe over the lumbar spinal cord to measure spinal cord blood flow, 16 male Sprague-Dawley rats were randomized into two groups: ischemic preconditioning (IPC, n = 8), and control (CTRL, n = 8). Rats in the CTRL and the IPC groups were subjected to 12 min of ischemia directly followed by 60 min of reperfusion. IPC rats received 3 min of IPC and 30 min of reperfusion prior to the 12-min insult period. Experiment 2: After instrumentation, the rats were randomized into three groups: control (CTRL, n = 7), ischemic preconditioning (IPC, n = 7), and time control (TC, n = 4). Rats in the CTRL and the IPC groups were subjected to the same ischemia and reperfusion protocol as above. The TC group was anesthetized for the same time period as the CTRL and the IPC groups, but had no ischemic intervention. Microspheres were injected at baseline and at 15 and 60 min into the final reperfusion. All rats were euthanized and tissue harvested for spinal cord blood flow analysis. In Experiment 1, there was a slight, significant difference in spinal cord blood flow during the ischemic period; however, this difference soon disappeared during reperfusion. In experiment 2, there was no difference in blood flow at any experimental time. The results of these experiments demonstrate that IPC slightly enhances blood flow to the spinal cord during ischemia; however, this effect is not sustained during the reperfusion period.